A Semantic Web pragmatic approach to develop Clinical ontolologies, and thus Semantic Interoperability, based in HL7 v2.xml messaging - Mendes, David (2012)
The ISO/HL7 27931:2009 standard intends to establish a global interoperability framework for Healthcare applications. However, being a messaging related protocol, it lacks a semantic foundation for interoperabil¬ity at a machine treatable level has intended through the Semantic Web. There is no alignment between the HL7 V2.xml message payloads and a meaning service like a suitable ontology. Careful application of Semantic Web tools and concepts can ease extremely the path to the fundamental concept of Shared Semantics. In this paper the Semantic Web and Artificial Intelligence tools and tech¬niques that allow aligned ontology population are presented and their ap¬plicability discussed. We present the coverage of HL7 RIM inadequacy for ontology mapping and how to circumvent it, NLP techniques for semi automated ontology population and discuss the current trends about knowl¬edge representation and reasoning that concur to the proposed achievement